The Relationship Of Socio-Economic Characteristics Of Vegetable Farmers In Increasing Income In Taeno Negeri Village Of Rumahtiga, Ambon Teluk District, Ambon City - Eunike Soplanit; Meilvis E. Tahitu; Ester D. Leatemia (Cita konsultindo, 2023)
This study aims to analyze the level of income of farmers in Taeno Negeri Rumahtiga Hamlet, Teluk Ambon, to determine the feasibility of vegetable farming in Taeno Hamlet and to examine the relationship between the socio-economic characteristics of farmers through age, education level, land area, number of dependents, experience, motivation, selling price and production cost. . The analysis used in this research is income analysis, feasibility analysis of B/C ratio (Beneift and Cost ratio) and correlation test (Pearson Product Moment). The results showed that the average income of leaf vegetable farmers in Taeno Negeri Rumahtiga was Rp.220,511,851,- per year. The results of the benefit cost ratio analysis show that the value of the ratio is 2.9 > 1 (more than one). Thus, leaf vegetable farming in Taeno Hamlet is feasible. The Pearson correlation test shows the successive values ​​of age, land area, number of dependents, experience, motivation and selling price (0,89,1,17,0,92,088,1,00,0,85). Education level and production costs have a weak correlation (0.27, 0.31). The level of relationship is weak because the farmers of Taeno Hamlet have a low level of education, besides that the higher the costs incurred by farmers, the smaller the income received.